2003
DOI: 10.1074/jbc.m209942200
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the in Vivo Folding of the Prion Protein

Abstract: Misfolding of the mammalian prion protein (PrP) is implicated in the pathogenesis of prion diseases. We analyzed wild type PrP in comparison with different PrP mutants and identified determinants of the in vivo folding pathway of PrP. The complete N terminus of PrP including the putative transmembrane domain and the first ␤-strand could be deleted without interfering with PrP maturation. Helix 1, however, turned out to be a major determinant of PrP folding. Disruption of helix 1 prevented attachment of the gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 68 publications
(60 reference statements)
3
64
1
Order By: Relevance
“…In this context it is important to note that in mammalian cells PrP⌬GPI is mainly unglycosylated, but in contrast to gPrP⌬GPI and pPrP⌬GPI expressed in yeast, it is N-terminally processed. In the same study we showed that PrP containing a nonfunctional C-terminal GPI anchor signal sequence is both N-terminally processed and core-glycosylated (10). Further biochemical analysis revealed that gPrP⌬GPI (Fig.…”
Section: Prp Targeted To the Er Is Unprocessed And Interferes Withmentioning
confidence: 74%
See 4 more Smart Citations
“…In this context it is important to note that in mammalian cells PrP⌬GPI is mainly unglycosylated, but in contrast to gPrP⌬GPI and pPrP⌬GPI expressed in yeast, it is N-terminally processed. In the same study we showed that PrP containing a nonfunctional C-terminal GPI anchor signal sequence is both N-terminally processed and core-glycosylated (10). Further biochemical analysis revealed that gPrP⌬GPI (Fig.…”
Section: Prp Targeted To the Er Is Unprocessed And Interferes Withmentioning
confidence: 74%
“…Endo H Digestion and Secretion Analysis in N2a Cells-For Endo H digestion, cell lysates were prepared in 0.5% SDS, boiled for 10 min, and digested with Endo H (NEB) for 1 h at 37°C (10). After boiling in Laemmli sample buffer, the lysates were examined by immunoblotting.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations